Spatial-ecological approach in cirebon's peri-urban regionalization. Issue 1 (1st November 2022) - Dede, M; Asdak, C; Setiawan, I
Abstract: The environmental transformation from rural into urban is a regional development process, it usually happens to industrial countries and formed a peri-urban region. Understanding the peri-urban development is an attempt to analyze the potential changes in environmental quality due to landscape changes in Cirebon Regency. The method of determining a peri-urban region is based on the spatial-ecological approach that is not only to use administrative boundaries. This study aims to analyze the regionalization of Cirebon's peri-urban using spatial-ecological approach. Parameters to determine the region based on built-up area, road density, distance from Cirebon City, and residential population density. The Cirebon's peri-urban was obtained from overlay analysis and defined interval reclassification. This study shows that the Cirebon's peri-urban has an area of 76.83 km 2 which is divided into five sub-districts and 48 villages surrounding Cirebon City. This peri-urban is mostly in the western of Cirebon Regency. This phenomenon shows the development direction of Cirebon City (urban sprawl) is more dominant towards the western and northwest because of massive development in industries, services, and transportations.